Peranan Media Sosial Terhadap Persepsi Aktivis Mahasiswa FISIP UNDIP Sebagai Pemilih Pemula Dalam Pilpres 2014 - muhammad hafiizh; Puji Astuti; Wiwik Widyawati (Journal of Politic and Government Studies, 2015)
Social media is almost owned by the people of Indonesia, especially among young people such as students of HMJ - FISIP-UNDIP 2012. Sudents of HMJ - FISIP-UNDIP 2012 as beginner voters in the 2014 presidential election, used the social media like Twitter and Facebook as a means to improve the knowledge of the two candidates for the presidential election of 2014. The use of social media accounts by both candidates in the 2014 presidential election is a recent phenomenon. Social media is used by both candidates to introduce themselves and present their vision and mission or work program. The purpose of this study was to determine the extent of the role of social media in shaping perceptions of the student members of the Sudents of HMJ - FISIP-UNDIP 2012 about candidates in the 2014 presidential election. The method used is a survey research method with quantitative descriptive approach. The sampling method applied was random sampling. A sample of 40 was obtained. The data was collected by using a measuring instrument such as a Likert scale questionnaire. The analysis technique used in this research was descriptive analysis and cross tabulation analysis with the aid of a computer program that is the Statistical Program Packages For Social Science (SPSS) for Windows Release 16.0. . Keywords: Perception, Social Media, The presidential election.